« Morale laïque » à l’école : de la tentation conservatrice à l’éducation du citoyen numérique - François Durpaire (Éducation et Socialisation)
The announcement that ‘secular morality’ will be taught in schools from the beginning of the 2013 school year places the country’s national education system at a crossroads between a return to the origins of the Third Republic and the opportunity to define a pedagogy adapted to contemporary citizens, living in an increasingly open world (‘village-terre’ from Michel Serres). This new ‘civic and moral education’ could promote a pedagogy of dialogue, taking as its starting point the diversity of the students and by discussing values in terms of a digital culture that is their own. Under these conditions, it could be both a laboratory for an educational revolution—didactic moral teaching could invite the ‘de-abstraction’ of learning—and a foundation for democratic citizenship.